Rumble fish - Hinton, S. E. (New York, Viking Press, 1968)
Sixteen-year-old Mark and Bryon have been like brothers since childhood, but now, as their involvement with girls, gangs, and drugs increases, their relationship seems to gradually disintegrate.
Keywords: Social problems -- Fiction; Friendship -- Fiction